Dissecting Peroxiredoxin Catalysis: Separating Binding, Peroxidation, and Resolution for a Bacterial AhpC - Parsonage, Derek (Biochemistry, 2015)
Peroxiredoxins make up a ubiquitous family of cysteine-dependent peroxidases that reduce hydroperoxide or peroxynitrite substrates through formation of a cysteine sulfenic acid (R-SOH) at the active site. In the 2-Cys peroxiredoxins, a second (resolving) cysteine reacts with the sulfenic acid to form a disulfide bond. For all peroxiredoxins, structural rearrangements in the vicinity of the active site cysteine(s) are necessary to allow disulfide bond formation and subsequent reductive recycling. In this study, we evaluated the rate constants for individual steps in the catalytic cycle of Salmonella typhimurium AhpC. Conserved Trp residues situated close to both peroxidatic and resolving cysteines in AhpC give rise to large changes in fluorescence during the catalytic cycle. For recycling, AhpF very efficiently reduces the AhpC disulfide, with a single discernible step and a rate constant of 2.3 × 10(7) M(−1) s(−1). Peroxide reduction was more complex and could be modeled as three steps, beginning with a reversible binding of H(2)O(2) to the enzyme (k(1) = 1.36 × 10(8) M(−1) s(−1), and k(−1) = 53 s(−1)), followed by rapid sulfenic acid generation (620 s(−1)) and then rate-limiting disulfide bond formation (75 s(−1)). Using bulkier hydroperoxide substrates with higher K(m) values, we found that different efficiencies (k(cat)/K(m)) for turnover of AhpC with these substrates are primarily caused by their slower rates of binding. Our findings indicate that this bacterial peroxiredoxin exhibits rates for both reducing and oxidizing parts of the catalytic cycle that are among the fastest observed so far for this diverse family of enzymes. [Image: see text]